Episodic gamma-ray and neutrino emission from the low mass X-ray binary GRO J0422+32 - Vieyro, Florencia Laura (2012)
GRO J0422+32 is a member of the class of low-mass X-ray binary (LMXB) sources, discovered during an outburst in 1992. Along the entire episode (∼ 230 days) a persistent power-law spectral component extending up to ∼ 1 MeV was observed. These results suggest that non-thermal processes must be at work in the system. We apply a corona model to describe the spectrum of GRO J0422+32 during the flaring phase. We study relativistic particle interactions solving the transport equations for all type of particles self-consistently. We fit the electromagnetic emission during the plateau phase of the event and estimate the emission during an energetic episode, as well as the neutrino production. Our work leads to predictions that can be tested by the new generation of very high energy gamma-ray instruments.